Identifying the Determinants in the Choice of Destination for Polish FDI outside the EU - Salamaga, Marcin (Krakow Review of Economics and Management/Zeszyty Naukowe Uniwersytetu Ekonomicznego w Krakowie, 2016)
The purpose of this article is to identify the main factors determining the choice of Polish foreign direct investment (FDI) destination outside the EU. The research includes the cost, market, efficiency, legal, social and political factors which may be important in the search for the beneficiaries of FDI. Data from a survey conducted among companies investing in FDI or planning this form of investment were used in the analysis. To classify the companies, decision trees were used, and created in accordance with a CART algorithm. These research methods enable the creation of company profiles with similar investment policies in terms how they prioritize their choice of investment destination. The study showed that when choosing a destination for FDI in European countries that are not EU members, the legal and cost factors were the most important, while political factors were also important in non-European destinations. The prominence of the legal factors may mean that some Polish companies are interested in FDI in the form of financial flows (ie. capital in transit) and tax optimisation.